2021
DOI: 10.3390/sym13101886
|View full text |Cite
|
Sign up to set email alerts
|

Spin Experimentation with Unpolarized Colliding Beams at the LHC

Abstract: A brief recollection of the problems related to a significant hyperon polarization observed in pp-collisions is given with an emphasis on the general role of spin in the dynamics of hadron interactions. The old, unsolved problem of the observation of a significant hyperon polarization can provide new insights as a result of the measurements of energies at the LHC; in combination with other measurements, these can be used to tag the QGP formation in pp-collisions with colliding beams. Polarization studies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…So, the already existing experimental environment at the CERN LHC can be used to perform measurements at the highest accelerator energies. Reference [6] discusses this possibility. It could help to resolve the notorious problem of the energy dependence of spin effects.…”
Section: Contributionsmentioning
confidence: 99%